Portrayals of Cancer in Hingga Jumpa Lagi (2018): Understanding and Enhancing Health Literacy in the Screen Media - Nuruliza Roslan; Liyana Azmi; Muhammad Amin Mohamad Affendi (Department of Media and Communication Studies, Faculty of Arts and Social Sciences, University of Malay, 2024)
Indexed by MyCite